2002
DOI: 10.1007/s007740200023
|View full text |Cite
|
Sign up to set email alerts
|

Association of gene polymorphisms and bone density in Japanese girls

Abstract: Although some studies have reported a relationship between several candidate polymorphic genes and bone mineral density (BMD), little is known concerning the genetic factors influencing BMD in children. This study examined this relationship in healthy Japanese girls (n=125; age, 13.4 +/- 0.89 years; range, 12-15 years). We investigated allelic variants of the vitamin D receptor (VDR) gene, the estrogen receptor (ER) gene, the parathyroid hormone (PTH) gene, the Ca-sensing receptor (CaSR) gene, and the beta3-ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
24
1
6

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 18 publications
7
24
1
6
Order By: Relevance
“…Moreover, PTH BstB1 polymorphisms also showed a significant interaction on serum PTH (p = 0.010). These results support previous findings in Japanese girls [47].…”
Section: Bone Mineral Densitysupporting
confidence: 95%
“…Moreover, PTH BstB1 polymorphisms also showed a significant interaction on serum PTH (p = 0.010). These results support previous findings in Japanese girls [47].…”
Section: Bone Mineral Densitysupporting
confidence: 95%
“…This result supports previous findings in American premenopausal women [26] , Japanese postmenopausal women [27] and in Japanese girls [29] . However, we were not able to replicate the association between BstBI polymorphism and BMD in females, but were the first to show this association also in males.…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, PTH activates osteoblasts and stimulates osteoclast formation and resorption [25] . Only a few studies have shown an association between PTH BstBI polymorphism and BMD or bone dimensions [26][27][28][29] , while other studies have shown no such associations [30] .Thus far, numerous association studies examining the genetic susceptibility to osteoporosis on the population level have yielded inconclusive results [31] . This could partly be attributed to the heterogeneity of the genetic background of the population, for example, due to genetic stratification in recently admixed populations [32] .…”
mentioning
confidence: 96%
“…Several polymorphisms have been described in the gene encoding PTH, which may influence not only the secretion rate of the hormone in response to the CaSR signaling but also the efficiency of the hormone, as has been shown in bone metabolism studies (Katsumata et al 2002) and familial isolated hypoparathyroidism (FIH) (Miric & Levine 1992). This syndrome, characterized by hypocalcemia and hyperphosphatemia due to an inherited deficient secretion of biologically active parathormone, has been related to PTH gene mutations and polymorphisms (Ahn et al 1986, Sunthornthepvarakul et al 1999.…”
Section: Introductionmentioning
confidence: 99%